Natural killer cells from endurance-trained older adults show improved functional and metabolic responses to adrenergic blockade and mTOR inhibition - Luciele Guerra Minuzzi; Helena Batatinha; Christopher Weyh; Vidya Srokshna Balasubramanian Lakshmi; Carmen Fiuza-Luces; Beatriz G. Gálvez; Alejandro Lucia; Ana Maria Teixeira; Natascha Sommer; José Cesar Rosa-Neto; Fabio Santos Lira; Karsten Krüger (Scientific Reports)
Abstract Aging is associated with immune dysfunction, but long-term endurance training may confer protective effects on immune cell function. This study investigates how natural killer (NK) cell phenotypes, functional markers, and metabolism differ between endurance-trained and untrained older adults. Ex vivo expanded NK cells from endurance-trained (63.6 ± 2.1 years) and untrained (64.3 ± 3.3 years) males were exposed to adrenergic blockade (propranolol; 0–200 ng/mL) or mTOR inhibition (rapamycin; 10–100 ng/mL), both with or without PMA-induced inflammatory stimulation. Flow cytometry assessed NK subsets, activation (CD38, CD57, CD107a, NKG2D), senescence (KLRG1), and inhibitory markers (PD-1, LAG-3, TIM-3, NKG2A). Seahorse analysis measured metabolic parameters. Trained participants displayed healthier immune profiles (lower NLR, SII) and higher effector NK cells with lower cytotoxic subsets. Propranolol at 100 ng/mL blunted PMA-driven increases in CD57, CD107a, and NKG2D, while potentiating regulatory markers KLRG1, LAG-3, and PD-1 in the trained group, indicating stronger immunoregulation. With rapamycin, trained NK cells preserved NKG2D and CD107a at 10 ng/mL, maintaining cytotoxicity and degranulation. In contrast, at 100 ng/mL rapamycin plus PMA, trained NK cells shifted toward an effector phenotype with higher CD57 and CD107a, yet a blunted PMA-increased LAG-3 and TIM-3, suggesting resistance to exhaustion. PD-1 and KLRG1 remained elevated, reflecting balanced immune control. Mitochondrial analysis revealed that trained NK cells exhibited higher basal and maximal OCR, greater spare respiratory capacity, and OCR/ECAR ratio, reflecting superior metabolic fitness. These findings indicate that endurance-trained older adults have NK cells with greater functional adaptability, reduced senescence, and enhanced metabolism under inflammatory and pharmacological stress.